Ancestral African Bats Brought Their Cargo of Pathogenic Leptospira to Madagascar under Cover of Colonization Events - (:unkn) unknown (My University, 2023)
Madagascar is home to an extraordinary diversity of endemic mammals hosting several zoonotic pathogens. Although the African origin of Malagasy mammals has been addressed for a number of volant and terrestrial taxa, the origin of their hosted zoonotic pathogens is currently unknown. Using bats and Leptospira infections as a model system, we tested whether Malagasy mammal hosts acquired these infections on the island following colonization events, or alternatively brought these bacteria from continental Africa. We first described the genetic diversity of pathogenic Leptospira infecting bats from Mozambique and then tested through analyses of molecular variance (AMOVA) whether the genetic diversity of Leptospira hosted by bats from Mozambique, Madagascar and Comoros is structured by geography or by their host phylogeny. This study reveals a wide diversity of Leptospira lineages shed by bats from Mozambique. AMOVA strongly supports that the diversity of Leptospira sequences obtained from bats sampled in Mozambique, Madagascar, and Comoros is structured according to bat phylogeny. Presented data show that a number of Leptospira lineages detected in bat congeners from continental Africa and Madagascar are imbedded within monophyletic clades, strongly suggesting that bat colonists have indeed originally crossed the Mozambique Channel while infected with pathogenic Leptospira.
Keywords: African Research